EMPOWERING EDUCATORS THROUGH PROFESSIONAL DEVELOPMENT AND TRAINING - Nabillah Syifauzzuhrah (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2023)
Empowering educators through professional development and training is essential to enhancing teaching quality and addressing the evolving challenges of modern classrooms. This study explores how continuous, relevant, and collaborative professional development initiatives impact teachers’ pedagogical skills, confidence, and professional identity. Data collected from interviews, focus groups, and document analysis reveal that sustained support, leadership involvement, and a culture of collaboration significantly contribute to the effectiveness of professional learning. However, systemic barriers such as limited time, resources, and occasional misalignment of training content hinder the full realization of professional development benefits. The findings emphasize the need for educational policies and school leadership to prioritize and facilitate meaningful professional growth opportunities. Ultimately, well-designed professional development programs empower educators to become innovative and reflective practitioners, better equipped to meet the diverse needs of their students in a rapidly changing educational landscape.